Faktor-Faktor Risiko Kejadian Kaki Diabetik pada Penderita Diabetes Melitus Tipe 2 (Studi Kasus Kontrol di RSUP dr. M. Djamil Padang) - Rina Rina; Henry Setyawan; Heri Nugroho; Suharyo Hadisaputro; Tjokorda Gde Dalem Pemayun (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background : Diabetic foot is one of the chronic complications of diabetes mellitus and are the most feared by people who suffer of diabetes mellitus as it can lead to disability or even death. This more specific research on risk factors of the ethnic communities of the Minangkabau society. The purpose of this research is to prove the factors related to the incidence of diabetic foot in people with type 2 diabetes mellitus.Methods : The research applied with mix method were quantitative as the main approach (case control design) and qualitative as support (indepth interview). Target population is all people with a diagnosis of type 2 diabetes mellitus in Padang City, West Sumatera Province there were 172 respondent involved, consisting of 86 cases and 86 controls with concequtive sampling technique. Data analysis included univariat and bivariat analysis using the chi square test and mu ltivariate analysis using multiple logistic regression test.Results : Factors proven to correlate with the incidence of diabetic foot in patients with type 2diabetes mellitus are deformities in legs (p=<0,001), habit of smoking (p=<0,001), age ≥45 years (p=<0,001; OR=27,6; 95%CI=3,96-193,23), a series of ulceration on the legs (p=0,001;), and hypertension (p=0,001), with the probability of 95,88%. Protective factors on the incidence of diabetic foot in patients with type 2 diabetes mellitus is a gender (p=0,002).Conclusion : Risk factors to the incidence of diabetic foot are related of the deformities in the foot, smoking, age, leg ulceration and hypertension